Business Sustainability of SMEs In Malaysia - Foster, Bob; Rusnendar, Elan; Nurhastuti, Evi Sri; Purwanto, Eko; Setiawan, Diwan; Putri, Shinta Hartini (Civitas : Jurnal Pengabdian Masyarakat, 2024)
This study explores the outcomes of the "Talk Series" community engagement program, which aimed to enhance understanding and awareness of sustainable business practices among SMEs and stakeholders in Malaysia. The program effectively introduced key business sustainability concepts through a structured approach involving expert lectures and interactive discussions, including its benefits, challenges, and practical applications. The findings indicate that the program motivated participants to adopt sustainable practices, emphasizing their potential to improve business reputation, operational efficiency, and innovation while contributing to broader societal and environmental goals. However, the program faced limitations, including a restricted participant scope, short duration, and resource constraints among SMEs. This research highlights the effectiveness of knowledge-sharing initiatives in promoting sustainable business practices. It underscores the need for expanded, long-term engagement to support the broader adoption of sustainability in the SME sector. The outcomes of this program contribute to advancing sustainable economic and environmental practices in Malaysia, aligning with global sustainability objectives.